Immune Responses to Bacillus Calmette–Guérin Vaccination: Why Do They Fail to Protect against Mycobacterium tuberculosis? - Moliva, Juan I.; Turner, Joanne; Torrelles, Jordi B. (Frontiers in Immunology, 2017)
Mycobacterium tuberculosis (M.tb), the causative agent of tuberculosis (TB), is the current leading cause of death due to a single infectious organism. Although curable, the broad emergence of multi-, extensive-, extreme- and total-drug resistant strains of M.tb has hindered eradication efforts of this pathogen. Furthermore, computational models predict a quarter of the world’s population is infected with M.tb in a latent state, effectively serving as the largest reservoir for any human pathogen with the ability to cause significant morbidity and mortality. The World Health Organization has prioritized new strategies for improved vaccination programs; however the lack of understanding of mycobacterial immunity has made it difficult to develop new successful vaccines. Currently, Mycobacterium bovis Bacillus Calmette-Guérin (BCG) is the only vaccine approved for use to prevent TB. BCG is highly efficacious at preventing meningeal and miliary TB, but is at best 60% effective against the development of pulmonary TB in adults and wanes as we age. In this review, we provide a detailed summary on the innate immune response of macrophages, dendritic cells, and neutrophils in response to BCG vaccination. Additionally, we discuss adaptive immune responses generated by BCG vaccination, emphasizing their specific contributions to mycobacterial immunity. The success of future vaccines against TB will directly depend on our understanding of mycobacterial immunity.